The genus Notomicrus in Guadeloupe, with description of three new species (Coleoptera: Noteridae) - Manuel, Michael (Zootaxa, 2015)
The genus Notomicrus Sharp, 1882 is recorded from Guadeloupe for the first time. Examination of recently collected material revealed the presence of four species, of which three are described as new species so far endemic to Guadeloupe. Notomicrus sabrouxi sp. n. is akin to the continental Neotropical species N. gracilipes Sharp, 1882 and N. traili Sharp, 1882. Notomicrus chailliei sp. n. and N. femineus sp. n. are sibling species which diverge from each other by 3.4% of observed distance in cytochrome oxidase 1 sequences. The latter species seems to be comprised of only females, and is suspected to reproduce by obligate parthenogenesis. The fourth species is N. sharpi Balfour-Browne, 1939. These species are morphologically described notably through scanning electron microscopy study, and data on their distribution in the Guadeloupe archipelago and habitat preferences are presented and discussed.